Literature Circles to Improve Classroom Management in an Overcrowded English Class (2020)
ABSTRACT: This action research was aimed at improving classroom management in an overcrowded English class through literature circles in a public institution in Bello. Due to the COVID19 crisis the objective of the research had to be restructured to be centered on classroom management in two environments and exploring the possibility of implementing literature circles in a virtual environment. Data were collected using a journal, a focus group, an interview to the cooperating teacher and a students’ self-evaluation questionnaire. Data analysis showed that in virtual environments discipline issues and disruptive behaviors can emerge, it also showed that students could feel apprehensive about group work in a virtual environment, but with the teachers’ guidance it may be possible to implement the strategy.